Learning Module: Its Effects on Learning Competencies in Edukasyon sa Pagpapakatao 2 - Annile Presbitero-Brazal (Future Science / FSH-PH Publications, 2026)
This study determined the effectiveness of the learning module (LM) and the enhancement of the learning competencies of Grade 2 pupils in Edukasyon sa Pagpapakatao (EsP), in Naga Central School I, School Year 2023-2024. The descriptive-comparative method was used. There were 30 Grade 2 pupils in Naga Central School 1 who were involved in the study. Researcher-made test and evaluation-checklist were used to gather data. Mean, Standard deviation, Weighted Mean, Proficiency Level, t-test for dependent samples, and Cohen’s d were used to treat the data gathered. Conclusion drawn were: (1) the status of Learning Competencies of Grade 2 pupils in Edukasyon sa Pagpapakatao (EsP) along the K-12 Curriculum Guide showed Approaching Proficiency; (2) the design of the learning module played a crucial role in fostering an engaging and comprehensive educational experience; (3) the crafted learning module had a very high validity in terms of face, construct, and content; (4) the implementation of the learning module in Edukasyon sa Pagpapakatao (EsP) significantly enhanced pupil performance; (5) there was a significant difference between the pretest and post-tests of the pupils in Edukasyon sa Pagpapakatao (EsP); and (6) the learning module was effective in developing the competencies of Edukasyon sa Pagpapakatao (EsP) for Quarter 2.